Predicting Learning: Comparing Study Techniques, Perseverance, and Metacognitive Skill. (January 2022) - Gurung, Regan A. R.; Mai, Theresa; Nelson, Matthew; Pruitt, Sydney
Background: Instructors and students are on a continuing quest to identify predictors of learning. Objective: This study examines the associations between self-reported exam score and study techniques among students in two courses, Introductory Psychology and Computer Science. Method: We used an online survey to measure the extent students ( N = 249) used 10 techniques studied in cognitive science. We also measured students' perseverance, metacognitive skill, distractions, and procrastination. Results: Student use of specific study techniques varied between the two courses and a high utility technique, practice testing, was well used. Students reported low levels of spaced practice. Perseverance and metacognitive skills both correlated significantly with many of the study techniques. While no study techniques predicted exam scores in Introductory Psychology beyond variance predicted by GPA, the use of spaced practice predicted a significant portion of variance in students in Computer Science. Conclusions: Students' use of study techniques varies between their courses and while related to GPA and exam scores, are not unique predictors of variance in learning. Additional moderators and mediators of learning need to be identified. Teaching Implications: We discuss ways instructors can help prepare students in Introductory Psychology and key needs for future research on studying.